2020
DOI: 10.1016/j.coesh.2020.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Soil pathogens that may potentially cause pandemics, including severe acute respiratory syndrome (SARS) coronaviruses

Abstract: Soil ecosystems contain and support the greatest amount of biodiversity on the planet. A majority of this diversity is made up of microorganisms, most of which are beneficial for humans. However, some of these organisms are considered human pathogens. In light of the current severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) outbreak, one may ponder the origin of the next pandemic and if soil may represent a source of pathogens with pandemic potential. This review focuses on several bacterial, fungal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(47 citation statements)
references
References 55 publications
0
41
0
2
Order By: Relevance
“…Finally, emergencies such as the current COVID-19 pandemic may create new prioritization in research and exploring linkages between soils and human health considering the increasing literature recently published. 33-35…”
Section: Soil Bioremediation and Human Healthmentioning
confidence: 99%
“…Finally, emergencies such as the current COVID-19 pandemic may create new prioritization in research and exploring linkages between soils and human health considering the increasing literature recently published. 33-35…”
Section: Soil Bioremediation and Human Healthmentioning
confidence: 99%
“…Finally, according to World Health Organization (WHO), providing safe water, sanitation, hygiene (WASH), and waste management is essential to protect human health and prevent infectious and transmissible diseases outbreaks, such as the recent outbreak involving novel coronavirus disease (COVID-19) (Steffan et al, 2020 ; WHO, 2020 ). Thus, wastewater treatment is necessary, especially under COVID-19 conditions, where water shortage can present an obstacle in many countries for purification and cleansing purposes.…”
Section: Introductionmentioning
confidence: 99%
“…The factors affecting the transmission of virus in soil mainly include soil types, temperature, and pH values ( Collivignarelli et al, 2020 , Nunez-Delgado, 2020 , Steffan et al, 2020 ). However, there is a lack of data on the infectivity of SARS-CoV-2 in soil.…”
Section: Overview Of Possible Transmission Pathwaysmentioning
confidence: 99%
“…On the other hand, it has been shown that even significant changes in pH (from 3 to 10) do not seem to confirm the disappearance of SARS-CoV-2 ( Chin et al, 2020 ). A study examining the survival of enveloped virus (e.g., H5N1) in soil demonstrated that the virus did not survive in sandy topsoil but did survive in purchased construction sand and compost suggesting that different soil characteristics greatly impact virus survival ( Steffan et al, 2020 ).…”
Section: Overview Of Possible Transmission Pathwaysmentioning
confidence: 99%